Robust and efficient EBG-backed wearable antenna for ISM applications - Saeed Ayesha; Ejaz Asma; Shahid Humayun; Amin Yasar; Tenhunen Hannu (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2022)
A structurally compact, semiflexible wearable antenna composed of a distinctively miniaturized electromagnetic band gap (EBG) structure is presented in this work. Designed for body-centric applications in the 5.8 GHz band, the design draws heavily from a novel planar geometry realized on Rogers RT/duroid 5880 laminate with a compact physical footprint spanning lateral dimensions of 0.6 lambda 0 x 0.06 lambda 0. Incorporating a 2 x 2 EBG structure at the rear of the proposed design ensures sufficient isolation between the body and the antenna, doing away with the performance degradation associated with high permittivity of the tissue layer. The peculiar antenna geometry allows for reduced backward radiation and low specific absorption rate (SAR). With the inclusion of EBG, the gain of the antenna undergoes a considerable increase to 7.2 dBi with more than 95% reduction in SAR value. In addition, the front-to-back ratio also amplified to 13 dB. A rigorous analysis detailing the structural robustness is reported for varied bend angle configurations of the proposed antenna. To assess the suitability of the proposed design as a body-worn antenna, an experimental investigation is carried out on different parts of the body. Experimental findings are congruent with computationally obtained results, validating the applicability of the novel antenna structure for body-worn applications.